The Legal Position of Foso and Boboso Customary Criminal Sanctions within the Framework of the National Criminal Code in the Jurisdiction of the Sultanate of Ternate - Faisal Faisal; Robert Lengkong Weku; Nurlaila Kadarwati Papuluwa; Isyana Kurniasari Koronas; Arief Budiono (Journal of Law, Politic and Humanities, 2026)
Foso and Boboso have functional customary legal force within the scope of the Ternate customary community as informal law (living law) to maintain the order of the Ternate customary community, North Maluku. This study analyzes: (1) the legal position of the customary criminal sanctions of foso and boboso in the Se Atorang customary tradition in the Ternate Sultanate of North Maluku and (2) the prospects and challenges of transforming customary criminal law as additional punishment in Law Number 1 of 2023 concerning the Criminal Code in the Ternate Sultanate of North Maluku. The research method used in this study is an empirical legal research method with a live case study approach. The results of the study indicate that the origin of Article 66 paragraph (1) letter f provides recognition of customary sanctions against perpetrators of criminal acts. However, there are problems in its application. This is because customary criminal sanctions, known in Ternate customary law as "Foso se Boboso," are based on the Adat se-Atorang philosophy and the principle of the relationship between the Sultan and the People, which prioritizes the implementation of the "Ngofa se Nyeku" custom. Violations of norms, ethics, etiquette (politeness), and customary law by ngofa se nyeku members will be subject to tiered customary sanctions. Initial sanctions include stern warnings, advice, or guidance from traditional elders or the customary council (fala raha) or spiritual leaders (sowohi) within the customary structure of the sultanate in North Maluku.